A Significant Milestone in Thyroid Eye Disease Research in Nepal - Shrestha, Eliya (Nepalese Journal of Ophthalmology, 2025)
We invite all ophthalmology centres and clinicians across Nepal to participate in this collaborative effort. Together, we can strengthen evidence-based care for TED and foster future research benefiting patients nationwide.